2018
DOI: 10.2147/ceor.s155038
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and health care utilization pre- and post-laparoscopic radiofrequency ablation of symptomatic fibroids and laparoscopic myomectomy: a randomized trial of uterine-sparing techniques (TRUST) in Canada

Abstract: ObjectiveThe objective of this study was to compare laparoscopic ultrasound-guided radiofrequency ablation of fibroids (Lap-RFA) and laparoscopic myomectomy in terms of 1) health care utilization and 2) serious complication rates. The secondary objectives were comparison of subject responses to validated symptom and quality-of-life questionnaires. We hypothesized that Lap-RFA health care utilization and clinical outcomes would not be worse than those of laparoscopic myomectomy in the aggregate.Patients and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Lim et al 5 reported that laparoscopic Bongers et al 15 39 -23 -4.4 -3.1 -Brölmann et al 16 Garza-Leal 17 ----Braun et al 18 114 -60 6.8 -3.2 --Brucker et al 19 66 -24 10.0 -5.5 20.5 (5, 103) a 10.0 (2, 86) a Hahn et al 20 Krämer et al 21 Carrafiello et al 22 20 (15, 25) b ---Cho et al 23 -(10, 40) ---Cho et al 24 ----Chudnoff et al 25 126 -60 -9.0 (2, 60) a 5.0 (0, 29) a Galen et al 26 Guido et al 27 Berman et al 28 Chudnoff et al 29 47 -30 2. 30 Galen et al 31 140 (42, 290) a -4.5 (1, 11) b 4.0 (2, 10) a Garza-Leal et al 32 Robles et al 33 Ghezzi et al 34 25 (20, 45) a 18 c --Bergamini et al 35 Iversen and Dueholm 36 ----Iversen et al 37 Jiang et al 38 25 (20, 30) b ---Kim et al 39 18 -5 ---Lee et al 40 ----Marcos et al 41 36 -11 12.0 (8, 24) b --Meng et al 42 ----Rattray et al 43 73 -26 6.7 -3.0 -11.1 -7.6 Rey et al 44 17 (11, 44) b ---Turtulici et al 45 28 (16, 43) b ---Wu et al 46 -(20, 40) 2.5 c --…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al 5 reported that laparoscopic Bongers et al 15 39 -23 -4.4 -3.1 -Brölmann et al 16 Garza-Leal 17 ----Braun et al 18 114 -60 6.8 -3.2 --Brucker et al 19 66 -24 10.0 -5.5 20.5 (5, 103) a 10.0 (2, 86) a Hahn et al 20 Krämer et al 21 Carrafiello et al 22 20 (15, 25) b ---Cho et al 23 -(10, 40) ---Cho et al 24 ----Chudnoff et al 25 126 -60 -9.0 (2, 60) a 5.0 (0, 29) a Galen et al 26 Guido et al 27 Berman et al 28 Chudnoff et al 29 47 -30 2. 30 Galen et al 31 140 (42, 290) a -4.5 (1, 11) b 4.0 (2, 10) a Garza-Leal et al 32 Robles et al 33 Ghezzi et al 34 25 (20, 45) a 18 c --Bergamini et al 35 Iversen and Dueholm 36 ----Iversen et al 37 Jiang et al 38 25 (20, 30) b ---Kim et al 39 18 -5 ---Lee et al 40 ----Marcos et al 41 36 -11 12.0 (8, 24) b --Meng et al 42 ----Rattray et al 43 73 -26 6.7 -3.0 -11.1 -7.6 Rey et al 44 17 (11, 44) b ---Turtulici et al 45 28 (16, 43) b ---Wu et al 46 -(20, 40) 2.5 c --…”
Section: Discussionmentioning
confidence: 99%
“…1 [14−35]. Nonextirpative treatments included UAE (16 studies, n = 9555) [14−17,19,20,22−24,26−29, 31,33,34], FUS (4 studies, n = 1516) [16,18,30,35], and laparoscopic RFA (3 studies, n = 49) [21,25,32]. UAE, FUS, and laparoscopic RFA groups were compared with patients undergoing myomectomy (n = 34872, n = 20667, n = 47 for each comparison respectively) [14−35].…”
Section: Resultsmentioning
confidence: 99%
“…Data regarding quality of life as determined with the UFS-QOL were provided in 4 studies, 2 comparing UAE with myomectomy [26,34] and 2 comparing laparoscopic RFA with myomectomy [25,32]. Using this scale, higher scores indicate better quality of life.…”
Section: Quality Of Lifementioning
confidence: 99%
“…The relationship between RFA and infertility is rarely the focus [72]. However, individual papers address case reports comparing pregnancy rates after RIF with those after surgical treatment and find similar outcomes concerning pregnancy, live birth, and abortion rates [70,73].…”
Section: Managementmentioning
confidence: 99%